2009 IEEE International Conference on Microwaves, Communications, Antennas and Electronics Systems 2009
DOI: 10.1109/comcas.2009.5385960
|View full text |Cite
|
Sign up to set email alerts
|

A tunable Cavity Backed Slot Antenna (CBSA) for close proximity biomedical sensing applications

Abstract: Presented is a Cavity Backed Slot Antenna (CBSA) designed for integration into a biomedical radiometric sensor. The sensor is intended for close proximity health monitoring applications. An internal probe feed adds a novel approach to biomedical antenna design by isolating antenna feed currents from the body and providing frequency tuning of ~50MHz/mm as a function of probe length. Measurements and simulations performed with the CBSA in close proximity to a skin tissue phantom confirm that the antenna is a goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…7. As described in [16], the antenna is designed to meet the requirements for close proximity functionality of radiometric sensors in the presence of biological media. For instance, it is tunable to 50 MHz/mm of the feed length, broadband ( ) and very efficient (88%).…”
Section: B Cbsa For Close-proximity Biomedical Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…7. As described in [16], the antenna is designed to meet the requirements for close proximity functionality of radiometric sensors in the presence of biological media. For instance, it is tunable to 50 MHz/mm of the feed length, broadband ( ) and very efficient (88%).…”
Section: B Cbsa For Close-proximity Biomedical Sensingmentioning
confidence: 99%
“…Broad bandwidth enables high-resolution sensing and highly efficient antennas ensure the maximum detectable signal is delivered to the system, resulting in reduced measurement uncertainty. Details of the CBSA design are given in [16].…”
Section: B Cbsa For Close-proximity Biomedical Sensingmentioning
confidence: 99%
“…At present, the microwave radiation temperature measurement system based on the total power radiometer and Dicke radiometer has achieved a series of achievements [8][9][10]. However, the total power radiometer and Dicke radiometer has large temperature measurement error and low temperature measurement accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement result showed that the Dicke microwave radiometer with printed dipole antenna can track the trend of physical temperature change of tissue model, but the measurement error was very large. In 2009–2012, Bondst et al [ 2 , 3 , 4 ] improved the measurement antenna and designed an antenna probe with good directivity, which can radiate energy in uniaxial direction. In addition, they improved the system structure of the radiometer.…”
Section: Introductionmentioning
confidence: 99%